Youth empowerment in Algeria between knowledge formation and economic integration: An analysis in light of the enabling environment and governance - Louelhi, Rima; Seghour, Farid (International journal of economic perspectives, 2025)
This study seeks to examine the state of youth empowerment in Algeria by monitoring indices of demographic distribution, cognitive and economic empowerment within the institutional and organizational context from 2000 to 2023. The research employed a descriptive-analytical methodology, utilizing official national and international statistical data. The findings indicate that Algeria is seeing a notable youth surge, with individuals aged 15 to 29 constituting 20.81% of the overall population in 2023. The state has exerted significant efforts in cognitive empowerment, as demonstrated by the rise in enrollment rates, especially in higher education. Nonetheless, this dynamism has not corresponded with equivalent favorable outcomes economically, as youth unemployment rates persist at elevated levels, and their engagement in the labor market has diminished. The study indicated a constrained enabling environment, evidenced by poor governance metrics such as government effectiveness, accountability, and regulatory quality, which impedes the youth’s capacity to integrate effectively into the economy and society. The study suggests that empowering youth in Algeria necessitates a holistic approach that incorporates cognitive and economic empowerment within a more effective and transparent institutional framework.